Strategies to Improve Entertainment Tax Compliance: Study Case at the Office of UPT Region VI Bapenda Medan City - Rezeki, Sri Gusti; Maidalena (PT Maju Malaqbi Makkarana, 2025)
This study discusses strategies for improving entertainment tax compliance at UPT Region VI Bapenda Medan City, which is an important part of the Regional Original Income (PAD). This study identifies the low level of entertainment tax compliance in Indonesia, which only reached 62% nationally and 55% in Medan City in 2022. Factors influencing non-compliance include weak supervision, low taxpayer awareness, and the complexity of tax mechanisms. Using a qualitative descriptive approach, this study explores the impact of non-compliance and proposes a compliance model-based strategy that includes four levels: (1)